Financial Markets, Credit Constraints, and Investment in Rural Romania - Chaves, Rodrigo A.; Sanchez, Susana; Schor, Saul; Tesliuc, Emil (Washington, DC: World Bank, 2013)
The report assesses the performance of financial markets in rural areas of Romania, based on three - rural household, rural enterprise, and financial intermediary - surveys, carried out in 1998, and other official data covering 1997. The study finds that rural financial markets perform rather poorly in three key dimensions: the degree of access to financial services by rural economic agents (enterprises and households) is very limited; this limited access hinders the ability of these agents to take advantage of the investment opportunities available in rural areas; and, these markets failed to allocate flows of credit to those agents with the most profitable investment opportunities. This poor performance is caused by an unfortunate combination of short term circumstances, structural factors, and government policies, and interventions. In particular, the degree of access to credit services by rural agents is very low, because several factors have combined, to weaken both the supply of, and demand for rural credit. The report suggests a detailed government strategy to correct the observed shortcomings of rural financial markets, and identifies new challenges likely to appear. Moreover, the Government could assist in increasing the availability of credit, by improving policies in financial markets, legal and regulatory framework, and, the ability of the financial sector to provide retail financial services.